A study of job involvement among high and low achieving persons - Srivastava, S.K. (2003)
The present study attempts to investigate the relationship between job involvement among high and low achieving persons. The sample consisted of 150 workers from Bharat Heavy Electricals Limited (B.H.E.L.) Haridwar Division. Tests of Achievement Motivation Scale by Mishra and Srivastava (1990) and Job Involvement Scale by Singh (1984) were administered on each worker. Results indicate that there is significant relationship between job involvement and need for achievement motivation and high achieving persons feel more involvement with their job as compared to low achieving persons. - Reproduced.
Keywords: Motivation; Personnel; Achievement motivation